The Effect of Angkung (Basella alba L.) Fruit Addition on Physicochemical Properties of Noodles - Domas Galih Patria; Sutrisno Adi Prayitno; Nur Agustin Mardiana (Food Science and Technology Journal (Foodscitech), 2022)
This study aims to determine the physicochemical properties of noodles added with angkung fruit juice as a natural dye. In addition, RVN have potential as healthy food because they contain antioxidant compounds derived from angkung fruit. The treatment in the study is addition of angkung juice, namely the addition of 0% (Control), 2% (RVN1), 4% (RVN2), and 6% (RVN3). Physicochemical analysis such as water content, water absorption index (WAI) and water-soluble index (WSI), color and texture profile. Research data were analyzed using a completely randomized design (CRD). Significant differences between data were analyzed using ANOVA followed by Duncan's multiple distance test (DMRT) at 5%. The water content of RVN samples ranged from 11.2% to 11.8% with Control sample (0% angkung juice) having the highest value, swelling index value is ranged from 51.05% to 51.09%, the WAI of RVN samples ranged from 4.90 g/g to 4.97 g/g with Control sample having the highest value, while the WSI value of RVN is ranged from 2.36% to 4.86%, the value of L is ranged from 60.82 to 66.78 while the value of a is ranged from 2.05 to 9.08 and the value of b with the addition of angkung juice is ranged from 19.81 to 25.01. The lowest value of hardness is control 6.91 mJ, ranged value of adhesiveness is 0.12-0.13 mJ, and lowest value of chewiness is control 4.81 mJ. In this research, red violet noodles with the addition of angkung fruit juice will be continued in the future by conducting sensory tests and testing health benefits in vitro and in vivo. It is expected that red violet noodles can be consumed by everyone as a healthy food.